2013
DOI: 10.1002/jobm.201200316
|View full text |Cite
|
Sign up to set email alerts
|

Toxic behavior of silver and zinc oxide nanoparticles on environmental microorganisms

Abstract: Silver and zinc oxide nanoparticles (Ag and ZnO NPs) are widely used as antimicrobial agents. However, their potential toxicological impact on environmental microorganisms is largely unexplored. The aim of this work was to investigate the sensitivity and adaptability of five bacterial species isolated from sewage towards Ag and ZnO NPs. The bacterial species were exposed to increasing concentration of nanoparticles and the growth inhibitory effect, exopolysaccharides (EPSs) and extracellular proteins (ECPs) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…The cultures that showed a long lag were inhibited at higher nanoparticle concentrations. It has been suggested that bacteria probably adapt to the nanoparticles or modify them to make them less toxic during the lag period [31]. Such adaptation by some bacteria could give them a survival advantage and this could lead to disturbance in composition of bacterial populations in soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultures that showed a long lag were inhibited at higher nanoparticle concentrations. It has been suggested that bacteria probably adapt to the nanoparticles or modify them to make them less toxic during the lag period [31]. Such adaptation by some bacteria could give them a survival advantage and this could lead to disturbance in composition of bacterial populations in soil.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have used pure cultures of ecologically important isolates to study the effects of silver and zinc oxide nanoparticles [29][30][31][32][33]. Similar disturbances in soil bacterial communities caused by the same nanoparticles have also been reported [34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 92%
“…In soil, TiO 2 NPs inhibited the growth of Bacillus megaterium , Pseudomonas fluorescens , Azotobater vinelandii , and B. brevis ; however ZrO 2 (zirconia) NPs did not show similar effects on these strains . Both Ag and ZnO NPs inhibited the growth of B. subtilis , B. barbaricus , and P. aeruginosa ; however with time, the strains were able to adapt to the toxic effects presumably by causing the NPs to agglomerate into less toxic micro particles, as indicated by dynamic light scattering results showing the particle size increased with time . B. subtilis and P. fluorescens were susceptible to the toxicity of Al 2 O 3 , TiO 2 , ZnO, and SiO 2 NPs; ZnO caused complete mortality in the strains, while Al 2 O 3 , TiO 2 , and SiO 2 NPs resulted in mortality rates of between 40 and 70%, depending on the strain .…”
Section: Effects Of Nanoparticles On the Growth Of Microbes Relevant mentioning
confidence: 99%
“…Zinc in the form of nano zinc-sulphate and nano zinc-methionine in a dose of 80 mg/kg in poultry) was found to improve growth performance, but especially zinc-nano-sulphate decreased growth performance in the broilers (Table 1). The disadvantage of the administration of nano zinc-sulphate is the possibility of contamination of the environment, as the element is transferred by sewage, although in smaller quantities than when conventional zinc forms are used (Dhas, 2014).…”
Section: Efficiency In Animal Productionmentioning
confidence: 99%